Sistem Pendukung Keputusan Pegawai Berprestasi Pada KSPPS BMT ALHIKMAH Weleri Dengan Metode SAW (Simple Addtive Weighting) - NUR ROKHMAN; Edy Siswanto; Nia Novitasari (LPPM Politeknik Pratama Kendal, 2021)
Employee Performance Assessment is used to evaluate the work of all employees or employees either quantitatively or qualitatively. Sometimes the problem of subjectivity in employee performance appraisals is often unavoidable, making it difficult to measure the parameters in the system. Based on this, to help determine the employee's work performance assessment, a decision support system is needed that can provide appropriate results in employee performance with predetermined criteria including Work Spirit, Discipline, Work Results, Responsibility. Based on the description, the author proposes to make